Children's University: How Does It Make a Difference?. (January 2022) - Aral, Neriman; Kartal, Metin; Deniz Gülleroğlu, Hamide; Aslan, Berna; Özdoğan Özbal, Ece; Aydos, Sebahat; Kadan, Gül; Dinçer, Ayşemine
Last five decades have witnessed the comprehensive growth of science education around the world as the science is regarded as the major tenets of innovation and economic growth. Various extant studies on science education have concentrate on how to deliver and put the science in both curriculum and classrooms. However, there are rarely researches on the evaluation of the science curriculum and its impact on the scientific skills. Likewise, despite the science curricula being implemented from the 2009 onward in Ankara Children's University, they have not yet been evaluated so far. This is the why it is essential for the evaluation of them due to the changes in the national science curricula and technological developments. This study aims at evaluating to update, change, or reform the science curricula in terms of learning objectives, content, learning activities, and the evaluation. Utilizing the mixed method, the study group was composed of 1, 218 participating children and nine science educators. Program evaluation and semi-structured interview forms were developed to collect the data. Then, the QUAN&QUAL data were analyzed by the programs. The findings are as the followings: the curricula meet the expectations of children and help them to learn something new and to develop the skills to use in daily lives. Moreover, the top three things mostly liked are the play-based activities, learning something new and learning further about animals. Science educators have mentioned that children's sense of curiosity, their active participation, and questions throughout the enactment of the science curricula made them happy.